International accounting: accounting quality after adoption of international accounting standards in Brazil (Research, Society and Development, 2020)
The International Accounting Standards (IFRS) aim to promote accounting communication worldwide and thus contribute to the exchange of capital, ensuring transparency and harmonization of financial statements. The present study aims to verify the Brazilian accounting improvement after adoption of the International Accounting Standards. To achieve the proposed goals we measure the number of words present in the explanatory notes published in periods before and after the adoption of the IFRS. The sample is composed of companies listed on the Brazilian Stock Exchange in the cyclical consumer sector; trade subsector and in the Textiles, Clothing and Footwear segment in Brazil, excluding the company Grazziotin S.A because it did not publish its explanatory notes in the years prior to 2010, when it became mandatory the publication in accordance with the IFRS. For data analysis, a simple linear regression is performed, and as an additional test, we calculated the general average and average per company. The results indicate that the number of words present in the explanatory notes increased after the adoption of the IFRS, contributing to more disclosure of accounting information and, hence, improvement of the overall accounting quality.